MANAGEMENT OF ACUTE MYOCARDIAL INFARCTION IN PATIENTS PRESENTING WITH PERSISTENT ST-SEGMENT ELEVATION (ENDING) - Frans Van de Werf; Jeroen Bax; Amadeo Betriu; Carina Blomstrom-Lundqvist; Filippo Crea; Volkmar Falk; Gerasimos Filippatos; Keith Fox; Kurt Huber; Adnan Kastrati; Annika Rosengren; P. Gabriel Steg; et al. (Столичная издательская компания, 2016)
Management of acute myocardial infarction in patients presenting with persistent ST-segment elevation (ending).